Branding fashion muslim (studi analisis brand wearing klamby) - Alifa Nur Fitri; Silvia Riskha Fabriar; Mustofa Hilmi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
The halal industry in Indonesia is undergoing development. This is supported by 87.17% of Indonesia's population are Muslims. One of the growing industries is the Muslim clothing industry.Â Modest fashion, a term for fashion trends with a more polite and closed fashion concept. One of the famous Muslim fashions is Wearing Klamby. A local fashion brand from Yogyakarta whose collections have local content. This paper aims to see how Muslim fashion branding is used by Wearing Klamby. During of competition in the Muslim fashion business, branding is an important thing as a form of differentiation with other products, Brand can give life to a product. Branding Wearing Klamby as a product that loves the country is shown with the tagline